(untitled) (European Journal of Pure and Applied Mathematics, 2024)
This paper introduces the notion of a B-filter in a B-algebra (X, ∗, 0) and presents characteristics of its properties : for any a ∈ X, the set < a >B= a k : k ∈ Z form a B-ideal and B-filter of X. Moreover, this paper shown some properties of exponents on B-algebra.